S05.2 Challenges and Opportunities: Potentials in Research on AMR Gonococci. (13th July 2013) - Deal, C
Abstract : Although gonorrhoea has afflicted humans for centuries and the causative bacterium, Neisseria gonorrhoeae, was identified over a century ago, gonorrhoea remains a global public health problem. Stepwise acquisition of genetic mutations has conferred gradually increasing resistance to multiple antibiotics, thus limiting their usage for presumptive therapy. Until recently cephalosporins have remained the foundation of treatment, but growing evidence suggests that resistance is emerging. Even as researchers work to understanding the genetic mutations required for cephalosporin resistance, it is clear that new treatment options are needed. This presents a challenge as the number of new systemic antimicrobials evaluated and approved each year by regulatory agencies has steadily fallen over the past 30 years. Currently one new antimicrobial is undergoing clinical study as a potential treatment of gonorrhoea. An alternative strategy is to repurpose older antibiotics by studying the efficacy of dual therapy combinations of existing antimicrobials. Ultimately new antimicrobial development is needed now, since the development process can take more than a decade. Detecting and responding to emergence of multidrug resistant gonorrhoea remains a challenge. Rapid detection of resistant infections is facilitated by local antimicrobial susceptibility testing, which requires live organisms isolated by culture. However, as the use of nucleic acid amplification tests (NAATs) have expanded, the number of N. gonorrhoeae cultures performed by public health laboratories decreased rapidly and the capacity of laboratories to perform culture has declined. An alternative strategy is to develop molecular assays for detecting genetic mutations associated with resistance or susceptibility to specific antimicrobials to guide antibiotic selection by the clinician at the point of care. Even with this potential, molecular assays may not be able to supplant culture-based antimicrobial susceptibility testing for surveillance to detect novel resistance phenotypes and genotypes. Ultimately a gonococcal vaccine may be the most effective public health strategy.